Answer:
[tex]y(t) = \displaystyle\frac{-1}{t + c}[/tex]
Step-by-step explanation:
[tex]\frac{dy}{dt} = y^2[/tex]
[tex]\frac{dy}{y^2} = dt[/tex]
If we integrate both the sides, we can get y(t)
Integrating, both sides, we get
[tex]\displaystyle\int \displaystyle\frac{dy}{y^2}= \int dt[/tex]
[tex]\displaystyle\frac{y^{-1}}{-1} = t + c[/tex]
where, c is the integration constant.
[tex]\displaystyle\frac{-1}{y} = t + c[/tex]
[tex]y = \displaystyle\frac{-1}{t + c}[/tex]
Thus, the obtained y(t) is
[tex]y(t) = \displaystyle\frac{-1}{t + c}[/tex]